Pembuatan Aplikasi Buta warna untuk penderita buta warna - Adi Hartanto; Nur Ismawati (Fakultas Ilmu Komputer, 2018)
Color blindness is the reason a person is unable to distinguish certain colors. Color blindness is experienced by someone from birth because of lack or absence of pigment in the retinal cone cells of the eye. So that someone will be difficult to distinguish and identify colors. The purpose of making this color-blind application is to help people with color blindness and know the color by making color transfusion and color correction to display names, RGB and HSV values of a color. This Color Blind application is an Android OS application that will be embedded in a smartphone that can be easily used by people with color blindness